Effect of milrinone on the inflammatory response and NF-kB activation in renal ischemia-reperfusion injury in mice - Jung, Hong Soo; Joo, Jin-Deok; Kim, Dae-Woo; In, Jang Hyeok; Roh, Misun; Jeong, Jong-Tae; Noh, Seung June; Choi, Jin Woo (Korean journal of anesthesiology, 2014)
Milrinone increases intracellular adenosine 3',5'-cyclic monophosphate concentration and enhances vascular relaxation. Nuclear factor-kappa B (NF-kB) plays a key role in inflammatory responses during ischemia-reperfusion (I/R) injury. We aimed to investigate the effect of milrinone on the inflammatory responses and NF-kB activation in renal I/R injury in mice. Thirty C57BL/6 mice were allocated into 3 groups. In group S (n = 10), only right nephrectomy was done. In group C (n = 10), the left kidney was subjected to 30 min of ischemia after right nephrectomy. In group M (n = 10), milrinone (5 µg/kg) was administered before ischemia. After 24 hours of reperfusion, the serum creatinine was measured, kidney samples were obtained for histology, and expressions of NF-kB and proinflammatory cytokines were analyzed. In group C, the serum creatinine concentration was markedly elevated, compared with group S. Creatinine concentration in group M was also elevated, but it was significantly lower than that in group C. Histologic evidence of renal damage was severe in group C, but it was improved in group M. In groups C and M, expression of NF-kB, tumor necrosis factor-α (TNF-α), intercellular adhesion molecule-1 (ICAM-1), monocyte chemoattractant protein-1 (MCP-1) and macrophage inflammatory protein-2 (MIP-2) mRNA increased significantly compared with group S (P < 0.05). But group M showed a lower expression of NF-kB, TNF-α, ICAM-1, MCP-1 and MIP-2 mRNA than group C (P < 0.05). Milrinone treatment attenuates the renal inflammatory response and activation of NF-kB, resulting in improvement of renal function and tissue injury.